2020
DOI: 10.1155/2020/1042451
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective Potential of the Natural Artocarpin against In Vitro UVB-Induced Apoptosis

Abstract: Apoptosis, a well-known pattern of programmed cell death, occurs in multicellular organisms not only for controlling tissue homeostasis but also for getting rid of severely damaged cells in order to protect the redundant growth of abnormal cells undergoing cancerous cells. The epidermis of the human skin, composed largely of keratinocytes (KCs), is renewed continuously. Therefore, KCs apoptosis plays a critical role in the maintenance of epidermis structure and function. However, regulated cell death can be di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…We reported that the NAR pretreatment prevents membrane rigidification induced by ROS and nitrite. Our previous data supported that NAR reduces lipid peroxidation products (LPOs) in vitro [33]. In addition, it has been shown that a topical treatment with artocarpin on hairless mice before UVB exposure decreases LPOs [30].…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…We reported that the NAR pretreatment prevents membrane rigidification induced by ROS and nitrite. Our previous data supported that NAR reduces lipid peroxidation products (LPOs) in vitro [33]. In addition, it has been shown that a topical treatment with artocarpin on hairless mice before UVB exposure decreases LPOs [30].…”
Section: Discussionsupporting
confidence: 77%
“…Sorting from low, moderate, and high amounts of UVB, the diverse features of cell death can be induced by running from apoptosis without inflammation, to apoptosis with a proinflammatory cytokine, and eventually up to necrosis with inflammation [35]. Our previous data showed that apoptosis 9 Oxidative Medicine and Cellular Longevity induced with a physiological dose of 55 mJ/cm 2 UVB was initiated by CPD lesions in DNA as well as ROS production, and mediated by caspase-3 and 8 activation [33]. In this work, we investigated other relevant markers of apoptosis to analyze the complete UVB response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations